Training manual - gender mainstreaming in Caribbean trade policies and programmes : promoting gender equality for improved trade and development (ITC GenevaCH, 2014)
Aims to increase awareness of the value of mainstreaming gender into the Caribbean's trade and economic development agenda, and improve participants' gender mainstreaming skills.\n
Keywords: GENDER ROLES